Springtime dandelion control in turfgrass using conventional and organic methods - Raudenbush, Zane (Kansas State University, 2012)
Common dandelion (Taraxacum officinale Weber) is an important perennial weed in turfgrass. Fall is considered the optimal time for postemergence herbicidal control of dandelions; however, applications in spring, when volatility damage to surrounding plants is an additional concern, are often needed. Therefore, we conducted research to determine the volatility of common broadleaf herbicides, and their efficacy when applied at spring and fall application timings. Volatility was determined by applying herbicides to turfgrass and using potted tomatoes as indicator plants. Tomatoes exposed to turfgrass treated with Trimec Classic, Confront, Surge, Escalade 2, and Imprelis exhibited little or no volatility damage, while exposure to Speedzone, 4 Speed XT, and Cool Power caused significant damage. In general, herbicides causing little or no damage were amine formulations. Two field studies determined the effect of spring and fall application timing on dandelion control with several herbicides. Herbicide applications in the spring coincided with dandelion anthesis stages: pre-bloom, peak bloom, and post-bloom. Results were dependent on dandelion pressure in the studies. In 2010, with lower pressure, there were no differences among herbicides at any spring timing when dandelion control was evaluated after one year; all herbicides gave ≥ 80% control. In 2011, with higher dandelion pressure, Imprelis SL and 4 Speed XT provided ≥ 96% dandelion control at the spring pre- and post-bloom timings, which was better than Surge, Escalade 2, Cool Power, and Confront. The best choices for spring efficacy combined with minimal to no volatility were Escalade 2 and Trimec Classic. Finally, because interest in organic dandelion control is increasing, we compared several organic weed control tactics with a conventional herbicide. In a two-year field study, the conventional herbicide gave much better control (> 96%) than any organic method. Horticultural vinegar corn gluten meal, and fertilizer-only gave < 25% control, while hand-weeding gave 58 to 71% control. While hand-weeding was the best of the organic tactics, the time required was considered prohibitive for turfgrass managers, unless initial weed levels were very low.
Keywords: Volatility; Taraxacum officinale; Organic weed control; Application timing; Herbicide volatility; Turfgrass weed control; Agriculture, General (0473); Agronomy (0285); Horticulture (0471)